2021
DOI: 10.3390/su13094901
|View full text |Cite
|
Sign up to set email alerts
|

Twitch as a Techno-Pedagogical Resource to Complement the Flipped Learning Methodology in a Time of Academic Uncertainty

Abstract: Flipped learning methodology has the potential to be combined with a multitude of didactic actions and techno-pedagogical resources that are adapted to the needs of the student. Access to resources and training outside the classroom can be carried out from various platforms. Following this line, Twitch is an interactive video transmission platform that is presented as an interesting digital resource to enhance the motivation of students in turning over learning moments. The objective of the study is to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 54 publications
(68 reference statements)
2
9
0
1
Order By: Relevance
“…The analyses revealed that learners had enhanced motivation levels when the instruction followed a flipped model which provided support to previous studies (e.g. Chang & Hwang, 2018;Davies, Dean & Ball, 2013;Girgin & Cabaroglu, 2021;Pozo-Sanchez et al, 2021), and satisfaction-being in direct relationship with motivation-also proved to be quite high which is again consistent with earlier work (Aguayo Vergara et al, 2019;Enfield, 2013;Gilboy, Heinerichs & Pazzaglia, 2015;McCarthy, 2016). Karaoglan Yılmaz (2021), in particular, found that adding questions into video content and some other support tools into the system led to enhanced course satisfaction which in turn increased engagement and motivation.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 88%
“…The analyses revealed that learners had enhanced motivation levels when the instruction followed a flipped model which provided support to previous studies (e.g. Chang & Hwang, 2018;Davies, Dean & Ball, 2013;Girgin & Cabaroglu, 2021;Pozo-Sanchez et al, 2021), and satisfaction-being in direct relationship with motivation-also proved to be quite high which is again consistent with earlier work (Aguayo Vergara et al, 2019;Enfield, 2013;Gilboy, Heinerichs & Pazzaglia, 2015;McCarthy, 2016). Karaoglan Yılmaz (2021), in particular, found that adding questions into video content and some other support tools into the system led to enhanced course satisfaction which in turn increased engagement and motivation.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 88%
“…First, our data reveal that participants mostly held positive perceptions of FCM learning integrated with web 2.0 tools (Wulandari, 2017;Knezevic, Zupanec, & Raduvolic, 2020). Second, in line with the literature our participants' self-reported motivation results point to an enhanced motivation for learning (Abdelrahman et al, 2017;Pozo-Sanchez, Lopez-Belmonte, Fuentes-Cabrera, Lopez-Nunez, 2021) and engagement of students (Bajurny, 2014;Alsowat, 2016). Third, our findings provide an insight into a variety of perceived pedagogical benefits of flipped language teaching integrated with web 2.0 tools.…”
Section: Discussionsupporting
confidence: 86%
“…We believe that the FC training method helps students break out of the learning routines they previously followed, and provides more incentives for students in the positive spirit of autonomy, positivity, cooperation, inquiry, etc. that have been emphasized in the FC literature in the past [ 6 – 9 ]. The multi-faceted skill assessment of EBM can better reflect the effectiveness of learning attitudes beyond the knowledge-oriented written test.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested the advantages of applying FC include: the improvement of students’ learning autonomy, the easier discovery of blind spots in students’ learning through students’ demonstration of pre-class reading, the more flexible presentation of teaching materials to encourage students’ classroom participation, the encouragement of students’ cooperation inside and outside the class, more efficient use of classroom time, etc. [ 6 – 9 ]. With the rapid development of information technology pushing up the trend of digital transformation of educational activities, FC has received great attention from various educational fields [ 5 , 7 ], the FC model has also been increasingly applied to the field of clinical teaching in recent years, including medical, pharmacy, nursing, and other health science fields [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation